2014
DOI: 10.1007/s13346-014-0206-y
|View full text |Cite
|
Sign up to set email alerts
|

Core-shell nanoparticulate formulation of gemcitabine: lyophilization, stability studies, and in vivo evaluation

Abstract: Core-shell nanoparticulate formulation of gemcitabine was prepared by incorporating gemcitabine in a hydrophilic bovine serum albumin (BSA) core surrounded by hydrophobic poly(DL-lactic acid-co-glycolic acid) (PLGA) shell with a particle size of 243 nm and encapsulation efficiency of 40.5 %. Prepared formulations were lyophilized, wherein several cryoprotectants were screened for product attributes such as cake appearance, reconstitution with water, and size constancy. Trehalose was screened as a lyoprotectant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…11Over the past few decades, there has been an increasing interest in the potential use of polymeric nanoparticles (NPs) as delivery vehicles for GEM, and studies have demonstrated that these nanocarriers can significantly enhance the anti-tumor efficiency of GEM and also reduce its systematic toxicities. [12][13][14][15] In this regard, Zhao et al 16 employed biocompatible lipid-polymer hybrid nanoparticles to co-deliver HIF1α siRNA and GEM for pancreatic cancer treatment in subcutaneous and orthotopic tumor models. The obtained results demonstrated the prolonged lifetime of GEM in the bloodstream and enhanced tumor tissue accumulation.…”
mentioning
confidence: 99%
“…11Over the past few decades, there has been an increasing interest in the potential use of polymeric nanoparticles (NPs) as delivery vehicles for GEM, and studies have demonstrated that these nanocarriers can significantly enhance the anti-tumor efficiency of GEM and also reduce its systematic toxicities. [12][13][14][15] In this regard, Zhao et al 16 employed biocompatible lipid-polymer hybrid nanoparticles to co-deliver HIF1α siRNA and GEM for pancreatic cancer treatment in subcutaneous and orthotopic tumor models. The obtained results demonstrated the prolonged lifetime of GEM in the bloodstream and enhanced tumor tissue accumulation.…”
mentioning
confidence: 99%
“…As shown above, the BSA nanocarriers were spherical, with good dispersion and uniformed sizes. Their sizes of 115.6±12.3 nm were only slightly increased to 120.7±11.2 nm after 10 days of incubation at 25°C, indicating sufficient stability for in vitro and animal studies [ 15 ]. Gene therapy, a promising tool for treating pancreatic cancer [ 9 ], can be facilitated by the use of nanoparticles for delivery.…”
Section: Discussionmentioning
confidence: 99%